2015
DOI: 10.17221/7981-vetmed
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Bacillus subtilis, Clostridium butyricum and Lactobacillus acidophilus endospores on growth performance, nutrient digestibility, meat quality, relative organ weight, microbial shedding and excreta noxious gas emission in broilers

Abstract: ABSTRACT:This study was conducted to evaluate the effects of Bacillus subtilis, Clostridium butyricum and Lactobacillus acidophilus (tri-strain probiotics, TSP) endospores in broilers. TSP can benefit the host animal by increasing nutrient absorption from the gastrointestinal tract and altering the intestinal ecosystem in poultry. A total of 500 day-old ROSS 308 mixed sex broiler chickens with an average initial body weight (IBW) of 45 g ± 0.6 g were used in this 35-day feeding study. Broiler chickens were ran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
48
2
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(62 citation statements)
references
References 29 publications
5
48
2
4
Order By: Relevance
“…This is in agreement with the findings of Hossain, Begum, and Kim (2015) who reported anincrease in the bursa weight of broilers fed tri-strain probiotics compared to the control group. Besides, Willis, Isikhuemhen, and Ibrahim (2007) also suggested that the bursa was the primary lymphoid organ in broilers and concluded that probiotics could increase the relative weight of bursa to body weight.…”
Section: Discussionsupporting
confidence: 93%
“…This is in agreement with the findings of Hossain, Begum, and Kim (2015) who reported anincrease in the bursa weight of broilers fed tri-strain probiotics compared to the control group. Besides, Willis, Isikhuemhen, and Ibrahim (2007) also suggested that the bursa was the primary lymphoid organ in broilers and concluded that probiotics could increase the relative weight of bursa to body weight.…”
Section: Discussionsupporting
confidence: 93%
“…Jin et al (1996) reported that dietary supplementation of 0.2% of Lactobacillus to male Arbor Acres broiler chicks from 10-day old to 38 days of growth significantly increased weight gain. Hossain et al, (2015) reported that broilers fed with Bacillus subtilis, Clostridium butyricum and Lactobacillus acidophilus (tri-strain probiotics) endospores shown increased body weight gain.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, some other investigators showed that the FCR was significantly reduced when the broiler chicks were fed with 0.5% yoghurt for 42 days (Mansoub, 2011), 0.2% of Lactobacillus from day 10 to 38 days (Jin et al, 1996), and Bacillus subtilis, Clostridium butyricum and Lactobacillus acidophilus (Hossain et al, 2015). However, Samarakoon and Samarasinghe (2012) reported that there is a linear increase in FCR of broiler chicken with their age.…”
Section: Feed Conversion Ratiomentioning
confidence: 96%
“…In growing-finishing pigs, dietary probiotics can improve growth performance and meat quality (Alexopoulos et al 2004;Ceslovas et al 2005;Shon et al 2005;Davis et al 2008). It has been well accepted that dietary probiotics could benefit animal performance by producing antibacterial substances in their intestines by competing with harmful gut flora and stimulating the immune system (Fuller 1992;Hossain et al 2015;Lan et al 2017). Multi-species preparations have an advantage on growth performances in livestock animals when compared to mono-and multi-strain probiotics (Timmerman et al 2004).…”
Section: Introductionmentioning
confidence: 99%